2011
DOI: 10.1017/s1751731110002399
|View full text |Cite
|
Sign up to set email alerts
|

Effect of compensatory growth on performance, carcass composition and plasma IGF-1 in grower finisher pigs

Abstract: A total of 48 female pigs (Large White 3 Landrace 3 Duroc cross) were used to determine whether a compensatory feed regime influenced performance, carcass composition and the level of plasma IGF-1. Pigs of initial age 73 days were fed a commercial diet at 0.70 of ad libitum (R) for 40 days followed by a return to ad libitum feeding for a further 42 days. The control group was fed ad libitum (A) throughout. Groups of animals on R and A feed regimes were slaughtered at the end of restriction period (SL1), 2 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
(39 reference statements)
0
12
1
Order By: Relevance
“…Increasing dietary CP level tended to increase ADG during the carryover period, which was different from those piglets that were severely restricted in nutrient intake during the treatment period and had signi cant compensatory growth during the re-alimentation period [37,38]. The ability for compensatory gain depends upon the extent, timing and duration of nutrient restriction [39,40].…”
Section: Discussionmentioning
confidence: 91%
“…Increasing dietary CP level tended to increase ADG during the carryover period, which was different from those piglets that were severely restricted in nutrient intake during the treatment period and had signi cant compensatory growth during the re-alimentation period [37,38]. The ability for compensatory gain depends upon the extent, timing and duration of nutrient restriction [39,40].…”
Section: Discussionmentioning
confidence: 91%
“…(1986) reported no differences in the muscle or fat ratios compared with control pigs. Chaosap et al . (2011) indicated that there might be changes in the efficiency of retention of nutrients other than N, such as fat.…”
Section: Discussionmentioning
confidence: 99%
“…Chaosap et al . (2011) reported that compensatory growth after feed restriction had no effect on muscle tissue weight, whereas it did influence internal organ and fat deposition.…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicate that sufficiency in dietary protein and amino acid contributes to triggering compensatory growth in pigs. However, compensatory growth was only observed in some studies (Chaosap et al 2011, Martínez-Ramírez et al 2009, Martinez-Ramirez et al 2008, O'Connell et al 2006; in other studies, compensatory growth was incomplete or absent (Chiba et al 1999, Pond & Mersmann 1990, Skiba et al 2001, Yang et al 2008a. Therefore, how compensatory growth can be induced and the underlying mechanisms remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have since examined compensatory growth in growing pigs that have been subjected to restricted feed intake or protein restriction (Chaosap et al 2011, Fabian et al 2002, Heyer & Lebret 2007, Oksbjerg et al 2002. In these studies, compensatory growth was explored as a means of improving carcass meat quality, nutrient utility, and nitrogen excretion and thus improving pork production efficiency.…”
Section: Introductionmentioning
confidence: 99%